2013
DOI: 10.1080/00131881.2013.825164
|View full text |Cite
|
Sign up to set email alerts
|

Developing the use of diagrammatic representations in primary mathematics through professional development

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Moreover, Ben spent much time emphasising the links between the verbal and the symbolic representations, helping learners to see concrete examples of the role of the numerator and denominator in the symbolic representation of fraction. This finding was in line with Azuka (2009), Barmby et al (2014), Naidoo (2011), who revealed that the use of representations can be more effective when concrete and semi-concrete aids are used in teaching and learning of mathematics.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, Ben spent much time emphasising the links between the verbal and the symbolic representations, helping learners to see concrete examples of the role of the numerator and denominator in the symbolic representation of fraction. This finding was in line with Azuka (2009), Barmby et al (2014), Naidoo (2011), who revealed that the use of representations can be more effective when concrete and semi-concrete aids are used in teaching and learning of mathematics.…”
Section: Discussionsupporting
confidence: 83%
“…Muraka's study (2008) observed that the consistent and coherent use of one type of representation can bridge student understanding over time because of its focus on mathematical relationships and problem-solving processes. Many researchers argue that the use of representations can be more effective and when concrete and semi-concrete aids are used in teaching and learning of mathematics, the conceptual understanding is improved (Azuka 2009;Barmby et al 2014;Naidoo 2011). Representations commonly used in the early years of schooling include concrete materials, diagrams or pictures, symbols, spoken language and experiences and are used to present mathematical idea with the aim of making it accessible to learners (Green & Hall 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Visual representations (VRs) enable children to make connections between their existing experiences and mathematical concepts (Barmby et al, 2013). Additionally, VRs help students gain insight into more abstract ideas and support the problem-solving process (Gersten et al, 2009).…”
Section: Conceptual Understanding Through Visual Representationsmentioning
confidence: 99%
“…The importance of pupils' understanding and the use of different representations is widely noted in the mathematics education literature [76]. However, there is mixed evidence for efficacy [77].…”
Section: Models and Representationsmentioning
confidence: 99%
“…For example, greater use may or may not lead to changes in how representations are used in terms of classroom activity, but may change classroom talk. The increased use is also sensitive to forms of professional development [76].…”
Section: Models and Representationsmentioning
confidence: 99%